2015
DOI: 10.1097/mjt.0000000000000184
|View full text |Cite
|
Sign up to set email alerts
|

Use of Noninvasive Ventilation in Adult Patients With Acute Asthma Exacerbation

Abstract: Noninvasive ventilation (NIV) has been found to be beneficial for respiratory failure in many disease states; however, limited data are available supporting its use in acute asthma exacerbation. A retrospective chart analysis of adult patients admitted for acute asthma exacerbation and treated with NIV between January 2007 and December 2009 at a tertiary care community hospital was done. Ninety-eight patient encounters were identified. Mean age of the patients was 48.3 years, and 46% were male. Nineteen patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 14 publications
2
13
1
3
Order By: Relevance
“…One explanation for the marked difference in mortality in our study is that NIV may have been used mainly in patients with lower severity of illness and not in borderline patients who failed standard medical therapy (28,29). The low rate of NIV failure in our study (4.7%) is in contrast with the rate of 19.4% reported in a study of 98 patients with a severe acute asthma exacerbation who failed routine treatment treated with NIV in the emergency department (30). The low rate of NIV failure also provided additional evidence that NIV was being used selectively in a lower-risk group.…”
Section: Original Researchcontrasting
confidence: 56%
“…One explanation for the marked difference in mortality in our study is that NIV may have been used mainly in patients with lower severity of illness and not in borderline patients who failed standard medical therapy (28,29). The low rate of NIV failure in our study (4.7%) is in contrast with the rate of 19.4% reported in a study of 98 patients with a severe acute asthma exacerbation who failed routine treatment treated with NIV in the emergency department (30). The low rate of NIV failure also provided additional evidence that NIV was being used selectively in a lower-risk group.…”
Section: Original Researchcontrasting
confidence: 56%
“…Our failure rate for NIV was 4.5%, similar to a large American retrospective cohort from an electronic medical record database but less than other studies . Leatherman reports a failure rate of 17% across five studies .…”
Section: Discussionsupporting
confidence: 73%
“…Other studies of NIV in asthma also report low or no complication rates . The haemodynamic effects of positive pressure ventilation are also less marked in spontaneous breathing patients …”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A few uncontrolled studies and RCTs have compared NIV versus routine care in patients with acute asthma [55,56]. Uncontrolled studies have shown physiological improvements in selected patients, whereas the RCTs and a meta-analysis have not shown differences in clinically relevant outcomes when comparing NIV with usual care [57].…”
Section: Recommendationmentioning
confidence: 99%